PENGARUH JENIS DAN KONSENTRASI SEMI-REFINED CARRAGEENAN (SRC) SEBAGAI STABILISATOR TERHADAP KUALITAS ES KRIM - istini, sri; zatnika, achmad (Jurnal Sains dan Teknologi Indonesia, 2007)
Carrageenan are natural hydrocolloids which are used as gelling agent, suspending agent, emulsifier and stabilizer. Carrageenan was extracted from Eucheuma cottonii andEucheuma spinosum seaweed species. There are three types of carragenan that commonly found that are kappa, iota and lamda carrageenan. Semi-refined carrageenan (SRC) is a seaweed flour that must be extracted to recover refined carrageenan, it is expected has ability to subtitute the function of refined carrageenan so that it could economize the using of refined carrageenan. However the price of SRC is cheaper thanrefined carrageenan. Firstly this research determined the type of SRC that could be used as stabilizer in ice cream products. That compare between kappa,iota and combination of kappa-iota SRC. Ice cream is made by blend all ingredients needed with hot water (70 – 80 0C) than homogenized using mixer at high speed in 10 minutes than the formula readyto evaluate. The evaluating include pH, overrum, density, rate the sedimentation, air particle size and melting quality. The next experiment conducted to find out the better result from the selected concentration. From the experiment we conclude that kappa SRC permitted as stabilizer in ice cream at concentration 0,0168 %.